2017
DOI: 10.1016/j.antiviral.2016.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel small molecule inhibitors against NS2B/NS3 serine protease from Zika virus

Abstract: Zika flavivirus infection during pregnancy appears to produce higher risk of microcephaly, and also causes multiple neurological problems such as Guillain–Barré syndrome. The Zika virus is now widespread in Central and South America, and is anticipated to become an increasing risk in the southern United States. With continuing global travel and the spread of the mosquito vector, the exposure is expected to accelerate, but there are no currently approved treatments against the Zika virus. The Zika NS2B/NS3 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
125
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 61 publications
0
125
0
2
Order By: Relevance
“…Noting the strong structural similarity of the catalytic region between the ZIKV NS2B/NS3 and the HCV NS3/NS4A proteases, a similar repurposing approach was recently employed by others (Lee et al, 2017) who evaluated the inhibitory efficacy of 71 of the promising HCV NS3/NS4A inhibitors. As a result, Lee et al (2017) identified 10 compounds with IC50 values less than 50 μM.…”
Section: Discussionmentioning
confidence: 99%
“…Noting the strong structural similarity of the catalytic region between the ZIKV NS2B/NS3 and the HCV NS3/NS4A proteases, a similar repurposing approach was recently employed by others (Lee et al, 2017) who evaluated the inhibitory efficacy of 71 of the promising HCV NS3/NS4A inhibitors. As a result, Lee et al (2017) identified 10 compounds with IC50 values less than 50 μM.…”
Section: Discussionmentioning
confidence: 99%
“…ZIKV proteins other than NS5 also constitute potential druggable antiviral targets. This is the case with the N2B-NS3 trypsin-like serine protease, which plays a key role in virus replication by contributing to viral polyprotein processing (30), or with NS3 helicase activity (31). Due to the relevance of NS2B-NS3 function in the ZIKV life cycle, the search for inhibitors of the enzymatic activity of this complex is at the front line of antiviral discovery against ZIKV (30,(32)(33)(34).…”
Section: Reference(s) or Sourcementioning
confidence: 99%
“…This is the case with the N2B-NS3 trypsin-like serine protease, which plays a key role in virus replication by contributing to viral polyprotein processing (30), or with NS3 helicase activity (31). Due to the relevance of NS2B-NS3 function in the ZIKV life cycle, the search for inhibitors of the enzymatic activity of this complex is at the front line of antiviral discovery against ZIKV (30,(32)(33)(34). For instance, taking advantage of a previous work that identified inhibitors of the HCV protease by high-throughput screening of over 40,000 compounds (35), the same group have recently analyzed 71 of these nonpeptidic small molecules against ZIKV and found that 10 of them showed 50% inhibitory concentrations (IC 50 s) lower than 50 M, with IC 50 s of 5.2 M and 4.1 M for compounds 2 and 3, respectively (30).…”
Section: Reference(s) or Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…(Lei et al, 2016;Phoo et al, 2016;. Due to the relevance of NS2B-NS3 function in the ZIKV life cycle, the search for inhibitors of the enzymatic activity of this complex is at the front line of antiviral discovery against ZIKV Sahoo et al, 2016;Lee et al, 2017;Rut et al, 2017). NS4A and NS4B deregulate Akt-mTOR signaling to inhibit neurogenesis and induce autophagy (Liang et al, 2016).…”
Section: Proteinsmentioning
confidence: 99%